Analysis of Acid Alizarin Violet N Dye Removal Using Sugarcane Bagasse as Adsorbent - Mitter, Eduardo Kovalski [UNESP]; dos Santos, Graziely Cristina [UNESP]; Rodrigues de Almeida, Erica Janaina [UNESP]; Morao, Luana Galvao [UNESP]; Prates Rodrigues, Heide Dayane [UNESP]; Corso, Carlos Renato [UNESP] (Springer, 2012)
With the development of the textile industry, there has been a demand for dye removal from contaminated effluents. In recent years, attention has been directed toward various natural solid materials that are capable of removing pollutants from contaminated water at low cost. One such material is sugarcane bagasse. The aim of the present study was to evaluate adsorption of the dye Acid Violet Alizarin N with different concentrations of sugarcane bagasse and granulometry in agitated systems at different pH. The most promising data (achieved with pH 2.5) was analyzed with both Freundlich and Langmuir isotherms equations. The model that better fits dye adsorption interaction into sugarcane bagasse is Freundlich equation, and thus the multilayer model. Moreover, a smaller bagasse granulometry led to greater dye adsorption. The best treatment was achieved with a granulometry value lower than 0.21 mm at pH 2.50, in which the total removal was estimated at a concentration of 16.25 mg mL(-1). Hence, sugarcane bagasse proves to be very attractive for dye removal from textile effluents.
Keywords: Sugarcane bagasse; Textile; Dyes; Acid alizarin violet N; Adsorption